Socio-economic role of Pashmina goats in Changthang region - SHEIKH, F D; AZMAT, SHAMIMA; GANAI, T A S; MISRA, S S; AZMAT, SABIA (The Indian Journal of Animal Sciences, 2011)
The Changthang region of Ladakh has a huge genetic resource on the income of which the Changthangi people thrive. The main livestock reared by these people are Pashmina goat, Changthangi sheep and yak. The economics of pastoral farming in Changthang region were studied and the income from Pashmina goat was compared with other livestock sources. The present study reveals that Pashmina goats add to majority of the total income followed by sheep and yak. Since at present no breeding policy is followed in Changthang region, a well organized breeding policy upgraded by a scientific managemental practice can add a lot to the present existing income of the Changthangi people. Â